2014
DOI: 10.1021/am500356g
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Composite Membrane with Enriched CO2-philic Groups and Improved Adhesion at the Interface

Abstract: A novel strategy to design a high-performance composite membrane for CO2 capture via coating a thin layer of water-swellable polymers (WSPs) onto a porous support with enriched CO2-philic groups is demonstrated in this study. First, by employing a versatile platform technique combining non-solvent-induced phase separation and surface segregation, porous support membranes with abundant CO2-philic ethylene oxide (EO) groups at the surface are successfully prepared. Second, a thin selective layer composed of Peba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…H_ZIF-8 was homogeneously mixed with PVC-g-POEM polymer matrix without any apparent interfacial voids or particle aggregation, regardless of H_ZIF-8 content. We expected the good adhesion between H_ZIF-8 and PVC-g-POEM to provide effective gas permeation and separation properties, because compatibility between the filler and polymer matrix is of pivotal importance in MMMs [12,[34][35][36][37][38]. The maximum loading amount of H_ZIF-8 for robust free-standing MMMs was 30 wt%, above which the MMMs became too brittle to be installed in the time-lag machine, which operates under high vacuum conditions.…”
Section: Resultsmentioning
confidence: 99%
“…H_ZIF-8 was homogeneously mixed with PVC-g-POEM polymer matrix without any apparent interfacial voids or particle aggregation, regardless of H_ZIF-8 content. We expected the good adhesion between H_ZIF-8 and PVC-g-POEM to provide effective gas permeation and separation properties, because compatibility between the filler and polymer matrix is of pivotal importance in MMMs [12,[34][35][36][37][38]. The maximum loading amount of H_ZIF-8 for robust free-standing MMMs was 30 wt%, above which the MMMs became too brittle to be installed in the time-lag machine, which operates under high vacuum conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the polymer chains within the pores displayed lower mobility and were described as "chain rigidification", which would cause a decrease of gas permeance and an increase of selectivity. 25 In order to investigate the difference in the spread and penetration of coating solution on PES and PES/PANI substrates, the dynamic contact angle of coating solution on the substrats was recorded using 2.0 wt% PVAm coating solution as the dispense liquid. As shown in Fig.…”
Section: Rsc Advances Accepted Manuscriptmentioning
confidence: 99%
“…While recently more and more researchers are realizing the importance of porous membrane supports on the performance of composite membrane and attempt to figure out the suitable properties of substrates for fabricating composite membrane. [19][20][21][22][23][24][25][26] In the published studies, the surface properties of the substrates were mainly altered by varying the polymer concentration 21 and blending polyvinylpyrrolidone (PVP) or poly (ethylene glycol) (PEG) 23 in the casting solution. It was reported that the porous support membrane could exert an effect on the selective layer structure besides providing the mechanical support for fabricating composite membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low molecular weight poly(ethylene glycol) (PEG) with abundant polar ether groups could produce dipole-quadrupole interactions with CO 2 and has been recognized as an effective polymer to achieve high CO 2 permeability and CO 2 /other gas selectivity [18,21,22]. Numerous efforts have been devoted to explore PEGcontaining blend membranes [23], copolymer membranes [24] and hybrid membranes [25,26] for efficient CO 2 separation.…”
Section: Introductionmentioning
confidence: 99%